Objektifikasi dan Subjektifikasi Murid dalam Tiga Pranata Pendidikan: Keluarga, Sekolah dan Masyarakat - Azhar, Khairil; Robandi, Babang (SUKMA: Jurnal Pendidikan, 2022)
This paper tries to show how objectification tends to occur in family, community and school education. Theoretically, objectification is opposed to subjectification. Objectification means positioning children, students or individuals as objects of education. On the other hand, subjectification is their positioning as subjects or active agents of learning. For this reason, a ‘middle way’ conceptualization is needed so that a conception of education in families, schools and communities is obtained that is oriented towards facilitating the natural development of students’ potential or nature